PENGARUH TERAPI FOOT MASSAGE TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI DI DESA WUKIRSARI PATI - Afifah Nur Cahya Putri Ajeng; Sukesih, Sukesih; Heny Siswanti (Nusantara Hasana Journal, 2025)
Hypertension is a growing global health problem, characterized by systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg. It is often called "The Silent Killer" because its symptoms are subtle. This disease has the potential to cause serious complications such as heart disease, stroke, and kidney failure. Factors such as unhealthy diet, lack of physical activity, and increasing age contribute to the increasing prevalence of hypertension, as reported by the WHO and the Ministry of Health. This condition requires a comprehensive treatment approach, using both pharmacological and non-pharmacological therapies. One non-pharmacological alternative that is attracting attention is foot massage therapy. This therapy is based on the principle of stimulating acupuncture points in the feet, which can improve blood circulation, relieve muscle tension, and reduce stress hormones such as cortisol and norepinephrine. With its deep relaxation effect, foot massage not only has the potential to lower blood pressure but also improves sleep quality and reduces anxiety, thereby improving the overall quality of life for hypertensive patients. Several previous studies support the effectiveness of this therapy in significantly lowering systolic and diastolic blood pressure. This study aims to test the effect of foot massage therapy on blood pressure in hypertensive patients in Wukirsari Village, Tambakromo District, Pati Regency. The research design used was observational with a pre-test and post-test control method. The intervention group received 20 minutes of foot massage therapy every evening, while the control group received education about hypertension. Blood pressure measurements were conducted using a sphygmomanometer with systematic recording according to standard operating procedures, thus obtaining valid data regarding differences in blood pressure before and after the intervention. Methodologically, this study involved 35 hypertensive patients selected purposively based on predetermined inclusion and exclusion criteria. Primary data were collected through direct observation, interviews, and recording of blood pressure measurements, while secondary data were obtained from official sources such as community health centers (Puskesmas) and the Health Office. Data analysis was conducted descriptively to describe the parameters of each variable, and inferentially using t-tests (paired and independent) to test for significant differences between the intervention and control groups. The study results are expected to provide a strong scientific basis for the application of foot massage therapy as an alternative or complementary treatment for hypertension, while also opening opportunities for further research in this area.